Recombinant human granulocyte colony-stimulating factor. Effects on hematopoiesis in normal and cyclophosphamide-treated primates (The Rockefeller University Press, 1987)
We examined the in vivo effects of recombinant human granulocyte colony- stimulating factor (rhG-CSF) in primates (cynomolgus monkeys) treated with subcutaneous doses of rhG-CSF for 14-28 d. A dose-dependent increase in the peripheral white blood cells (WBC) was seen, reaching a plateau after 1 wk of rhG-CSF treatment. The elevation of WBC was due to an increase in the absolute neutrophil count. These results demonstrate that rhG-CSF is a potent granulopoietic growth and differentiation factor in vivo. In cyclophosphamide (CY)-induced myelosuppression, rhG-CSF was able to shorten the time period of WBC recovery in two treated monkeys to 1 wk, as compared to more than 4 wk for the control monkey. Its ability to significantly shorten the period of chemotherapy-induced bone marrow hypoplasia may allow clinicians to increase the frequency or dosage of chemotherapeutic agents. In addition, the increase in absolute numbers of functionally active neutrophils may have a profound effect in the rate and severity of neutropenia-related sepsis. Furthermore, the activities reported here indicate a potential role for rhG-CSF in the treatment of patients with myelodysplastic syndrome, congenital agranulocytosis, radiation-induced myelosuppression, and bone marrow transplantation.